PKM Meningkatkan Pengetahuan dan Keterampilan Mitra Tentang Kewirausahaan Bagi Kelompok Mitra Dusun Kanari Desa Mallongi-Longi Kabupaten Pinrang - Syafruddin Side; Hasri Hasri; Muh. Isbar Pratama; Muh Al Rasyid Ridho; Andi Muhammad Ridho SAP (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2022)
Abstract. The Community Partnership Program (PKM) activities were carried out in Mallongi-longi village, Lanrisang district, Pinrang district. The objectives of this activity are to: a) increase the knowledge and skills of partners about entrepreneurship for partner groups, b) increase the knowledge and skills of partners about managing corn harvests into economically valuable products, c) increase the knowledge and skills of partners about digital-based marketing. Partner problems are: a) Lack of knowledge and skills of partners about entrepreneurship for partner groups, b) Lack of knowledge and skills of partners about managing corn harvests into products of economic value, c) Lack of knowledge and skills of partners about digital-based marketing. The method used is training, discussion and counseling in collaboration between implementers and partners. This method is carried out to a group of 10 active partners out of 33 people for 4 days and then evaluation and monitoring are carried out periodically for 3 months. The results of this activity are: increased ability and knowledge of all partner members active about entrepreneurship, all partner members active can process corn into corn flour products and 3 partner members are able to do digital marketing.Keywords: Knowledge and skills, Product processing, Digital marketing, Corn Flour, Entrepreneurship.